The Krein-von Neumann extension of a regular even order quasi-differential operator - Minsung Cho (AGH Univeristy of Science and Technology Press, 2021)
We characterize by boundary conditions the Krein-von Neumann extension of a strictly positive minimal operator corresponding to a regular even order quasi-differential expression of Shin-Zettl type. The characterization is stated in terms of a specially chosen basis for the kernel of the maximal operator and employs a description of the Friedrichs extension due to Möller and Zettl.